Pengaruh Peran Syahbandar, Kemampuan Berkomunikasi, dan Implementasi ISM Code terhadap Keselamatan Pelayaran di Pelabuhan Penyeberangan Padang Bai, Bali - Davina Dwi Safitri (Indonesian Maritime Researchers and Lecturers, 2025)
This study aims to analyze the influence of the role of the Port Authority (Syahbandar), communication skills, and the implementation of the International Safety Management (ISM) Code on maritime safety at the Padang Bai Ferry Port, Bali. Maritime safety is a top priority in maritime transportation operations, which is heavily influenced by the effectiveness of the Port Authority's supervision, the communication skills between the ship's crew and port officers, and the level of ISM Code implementation as an international standard for ship safety and risk management. This research uses a quantitative method with an associative approach to determine the relationships between variables. Data were collected through the distribution of questionnaires to 100 respondents, including the Port Authority, ship crews, and port officers. Data analysis was conducted using SPSS version 26 with multiple linear regression tests. The results of the study indicate that all three independent variables have a positive and significant influence on maritime safety. The role of the Port Authority has the most dominant influence in ensuring the seaworthiness of ships and compliance with regulations. The implications of this study emphasize the importance of improving maritime communication skills and strengthening the implementation of the ISM Code as the foundation for a sustainable maritime safety system.